Sosialiasi dan Pelatihan Tarian Lebe dalam Rangka Pelestarian Budaya Bagi Kaum Muda - Demitriana Maubili Seran; Indriyati Indriyati; Stephanie P. A. Lawalu; Yasinta P. Peten; Marianus Kleden; Frans Nyong; Alfry Sinlae (Jurnal Nusantara Berbakti, 2024)
The lebe dance is a cultural heritage originating from Adonara Island, East Nusa Tenggara. As a traditional art form, lebe dance has cultural values that are important to maintain and preserve, especially for the younger generation in Watoone Village. In this community service activity the author focuses on efforts to preserve the lebe dance among young people in Watoone Village, especially students at Lamaholot 1912 Watoone Catholic Middle School. The methods used in this activity are approach, outreach and training. This community service activity revealed several obstacles faced by the community, especially young people, such as the lack of interest among young people in learning and practicing lebe dance, this is caused by the influence of the modern world which has dominated young people so that today's young people are more interested in the world. modern and without realizing it, people have ignored one of the characteristics or cultural identity of Watoone Village, namely the Lebe Dance. The author also analyzes the lack of support from the local government in promoting and documenting this traditional art